Tourism business startup: Recognizing opportunities and barriers to entry - Dias, Á. (Handbook of tourism entrepreneurship, 2024)
Entrepreneurship and start-ups are extremely important in the tourism sector, providing ‘new blood’ to the industry in terms of innovation, sustainability and competitiveness. Despite this importance, the research dedicated to these issues is still scarce and disperse. As such, this chapter aims to explore the topic of tourism start-ups from several perspectives: theoretical underpinnings of existing research, barriers, and opportunities. It converges with the proposal of a model that integrates the dimensions of human capital, social capital, and environment, highlighting the crucial role that place plays in the development of these factors and in start-ups.